EVALUASI MANAJERIAL PROGRAM TAHFIZ AL-QUR’AN DENGAN MODEL CIPP: UPAYA MENJAGA KONSISTENSI HAFALAN SISWA DI SMAN 2 BANDAR LAMPUNG - Nelma Elpayuni; Subandi Subandi; Septuri Septuri (STKIP Pesisir Selatan, 2026)
This study aims to evaluate the managerial implementation of the Qur’an memorization (tahfiz) program in maintaining students’ memorization consistency at SMAN 2 Bandar Lampung using the CIPP (Context, Input, Process, Product) model. This research employed a qualitative evaluative approach. Data were collected through interviews, observations, and documentation. The findings indicate that the program is relevant to strengthening students’ religious character, although the objectives have not been formulated in measurable terms. The program is supported by adequate resources; however, limitations remain in curriculum structure, facilities, and funding. The implementation process has been carried out, yet monitoring, coordination, and motivational reinforcement are not optimal. The program has a positive impact on students’ memorization achievement and religious attitudes, although memorization consistency has not been fully sustained. Strengthening managerial aspects is essential to ensure program sustainability.